1976
DOI: 10.1128/iai.13.6.1642-1646.1976
|View full text |Cite
|
Sign up to set email alerts
|

In vitro differentiation and pH sensitivity of field and cell culture-attentuated strains of transmissible gastroenteritis virus

Abstract: Characteristics of four transmissible gastroenteritis (TGE) virus field strains (Miller, Purdue, Bl, and V203) and four cell culture-attenuated strains (Purdue, SH, CKp, and Bl) were studied to find methods of differentiation between the two groups of viruses. TGE field virus strains did not replicate as well as attenuated strains at 37 C and could not be passaged serially for more than four to six passages at 33 C. There were clear differences in plaque size when the strains were compared. Field strains had a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0
2

Year Published

1987
1987
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 8 publications
0
10
0
2
Order By: Relevance
“…Biochemical and biophysical differences among field isolates and cell cultureattenuated TGEV have been reported [4,7], but serologic differences were not identified [13,14]. Using MAbs to Purdue TGEV in competitive assays, Delmas et al [3] demonstrated that the neutralization mediating determinants were highly conserved among TGEV strains.…”
Section: Discussionmentioning
confidence: 99%
“…Biochemical and biophysical differences among field isolates and cell cultureattenuated TGEV have been reported [4,7], but serologic differences were not identified [13,14]. Using MAbs to Purdue TGEV in competitive assays, Delmas et al [3] demonstrated that the neutralization mediating determinants were highly conserved among TGEV strains.…”
Section: Discussionmentioning
confidence: 99%
“…However, this virus showed marked instability at pH above its optimum pH of 6.5, when incubated for 24 hours (21). Similar to IBV, TGEV strains showed great variability in their stabilities to an acidic environment (12). Moreover, TGEV strains were generally heat-labile since they were inactivated in a few days at 37°C and in 10 minutes at 56°C (3,15,18).…”
Section: Discussionmentioning
confidence: 99%
“…La gastroenterite transmissible (GET) est une enterite neonatale mortelle, hautement contagieuse, causee par un coronavirus specifique de l'espece porcine; Ia GET est responsable de lourdes pertes economiques en production porcine. La relation entre Ie pouvoir pathogene du virus et d'eventuels marqueurs in vitro lies par exemple aux conditions de sa replication, fait encore l'objet de controverse [9,11,14,17]. Apres un certain nombre de passages en serie sur culture cellulaire, le virus OET perd une grande partie de son pouvoir pathogene.…”
Section: Introductionunclassified
“…Au-dela de cette dose (7 ug/ml) le metaperiodate affecte I'antigenicite non seulement de deux glycoproteines (E1 et E2) mais aussi de la nucleoproteine (NP) qui n'est pas glycosylee (fig. 7).DISCUSSIONLa thermosensibilite de la replication a ete proposee dans le passe comme marqueur de la virulence du virus de la OET[9,11]. Pourtant, recemment, a partir de huit souches du virus, Laude et coll [14].…”
unclassified